Constructing WH-Questions Througn An Error Analysis at Junior High School of Indonesia - Masruddin Masruddin; Karmila Karmila (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
This research aims at finding out the types of errors committed by the students in making wh questions. The researcher applies descriptive research. It is used to describe the errors of the students. in making wh-questions. The population of this research is the second year students of SMP Negeri 2 Bua Ponrang. The total number of population in this research is 240 students. The researcher uses purposive sampling technique in determining class VIII A. Therefore, the total number of sample in this research is 28 students. Based on the result of data analysis, the researcher concludes the types of error that the second year students at SMP Negeri 2 Bua Ponrang committed in making wh-questions are omission, simple addition, archi-form, alternating form, misordering, and miselection. The omission is dominant errors that the students made because from 1017 of total errors, 475 or 46.7% of the total errors are omission. Then, it followed by archi-form with the total errors is 275 or 28%, 155 errors of simple addition or 15.2%, 93 errors of misordering or 9.1%, 11 errors of alternating form or 1.1%, and the least types of errors is miselection with 8 errors or 0.8%.